Two new species of Syrphidae (Diptera) from Chukotka (Northern Russian Far East) - Barkalov, Anatolij V.; Mutin, Valerij A. (Zootaxa, 2014)
Two new species, Platycheirus beringiensis sp. n. and Cheilosia chukotana sp. n., are described from Chukotka (northern part of Russian Far East). The new Platycheirus is close to Platycheirus immarginatus (Zetterstedt), but differing by the following characters: fore tibia with a black stripe on posterior side; mid-femur without fine black curved hairs directed to the base of the femur; mid-tibia without long anteroventral hairs; abdomen black with fine brownish lustre on tergites. The new Cheilosia species is close to Ch. semifasciata Becker, but differs by its characteristic sharply raised central knob, and by lack of transversal stripe and indentation in anterior third of frons.